2000
DOI: 10.1111/j.1528-1157.2000.tb01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Granule Cell Neurogenesis After Status Epilepticus in the Immature Rat Brain

Abstract: Summary:Purpose: Several experimental paradigms of seizure induction that produce epilepsy as a consequence have been shown to be associated with the proliferation of dentate granule cells. In developing animals, the acute sequela of hilar damage and the chronic sequelae of spontaneous seizures and mossy fiber synaptic reorganization, in response to status epilepticus, occur in an age-dependent manner. We investigated seizure-induced granule cell neurogenesis in developing rat pups to study the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 21 publications
7
59
0
Order By: Relevance
“…Animals underwent pilocarpine-induced SE at P20 and BrdU injection to label dividing cells 4, 6, and 8 days later. We chose to inject during these times to capture the period of robust DGC division after pilocarpine-induced seizures (14,17). We then killed animals over the next 3 weeks to assess the survival of the newborn DGCs during the latent period, but be-…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animals underwent pilocarpine-induced SE at P20 and BrdU injection to label dividing cells 4, 6, and 8 days later. We chose to inject during these times to capture the period of robust DGC division after pilocarpine-induced seizures (14,17). We then killed animals over the next 3 weeks to assess the survival of the newborn DGCs during the latent period, but be-…”
Section: Resultsmentioning
confidence: 99%
“…Dramatic increase in the birth of DGCs, seen after an episode of pilocarpine-induced SE, has been demonstrated by others in pilocarpine, kainate, and kindling models, in both adult and immature animals (14,15,17,25). We previously found a ∼20% increase in DGC numbers in adult animals that developed epilepsy after SE at P20, suggesting a possible persistence of DGCs born in the weeks after SE (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This appears to occur after brief seizures, 9 kindling, 60,71,92 and after status epilepticus induced by chemoconvulsants such as pilocarpine 26,73 or kainic acid 45, 69 or status epilepticus induced by electrical stimulation. 82 Seizures following electroconvulsive shock also increase neurogenesis. 64,93 Other experimental insults that injure the brain cause increased neurogenesis also, such as experimental trauma or stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In mature rats, animal studies have confirmed that single episode of status epilepticus induced by pilocarpine [2] , kainic acid [3] and kindling [4] can increase cell proliferation in the subgranular zone of the dentate gyrus, cause neuronal loss in the hippocampus, and lead to aberrant sprouting of mossy fibers in the pyramidal cell region of CA3 and the supragranular zone of dentate gyrus. In immature rat, previous researches [5][6] have manifested that a prolonged seizure resulted in more neurogenesis but less cell loss and sprouting than it did in adult. However, other studies have demonstrated that neonatal seizures resulted in reduced neurogenesis [7][8] .…”
Section: Introductionmentioning
confidence: 96%